Developing Students’ Soft Skills Through Group-Work Method in Cost Accounting Learning - Evi Marlina, Maria Assumpta (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to explore the development of students’ soft skills by using group-work methods in Cost Accounting learning. This research is a classroom action research consisting of two cycles using the Kemmis and McTaggart models. The researcher conducted this research during the Cost Accounting learning process. The process involved two classes consisting of a total of 59 students. In the process of collecting data, the researcher used observation, group discussion, and documentation methods. The researcher conducted a reflection phase to formulate the results. The results showed that the group-work method implemented in the Cost Accounting learning process can improve students’ soft skills in an Accounting Study Program. The finding of this study is the students like the active learning model conducted using the work-group method. Students also like the mentoring program. Through this mentoring, interpersonal relationships between students and lecturers can be established, so students are more motivated to follow the learning process.